Adsorption of Crystal Violet onto an Agricultural Waste Residue: Kinetics, Isotherm, Thermodynamics, and Mechanism of Adsorption - Ilyasse Loulidi; Fatima Boukhlifi; Mbarka Ouchabi; Abdelouahed Amar; Maria Jabri; Abderahim Kali; Salma Chraibi; Chaimaa Hadey; Faissal Aziz (The Scientific World Journal)
Agricultural waste can be exploited for the adsorption of dyes, due to their low cost, availability, cost-effectiveness, and efficiency. In this study, we were interested in the elimination of crystal violet dye, from aqueous solutions, by adsorption on almond shell-based material, as a low-cost and ecofriendly adsorbent. The almond shells were first analyzed by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction; then, the influence of adsorbent dose, initial dye concentration time, and pH were studied to assess adsorption capacity under optimal experimental conditions. Experimental results indicate that almond shell adsorbent removes about 83% of the dye from the solutions at room temperature and in batch mode; the kinetic study showed that the equilibrium time is about 90 min, and the model of pseudo-second order could very well describe adsorption kinetics. The modulation of adsorption isotherms showed that retention follows the Langmuir model. The thermodynamic study has shown that the adsorption is endothermic (ΔH° > 0) and spontaneous (ΔG° < 0).